A violência infantil, com destaque ao abuso sexual, sob intervenções psicanalíticas - Portolani, Thaís Pamela (2019)
Introduction: Currently, the various forms of violence, including sexual abuse against children and adolescents, are being considered a serious public health problem. Throughout the history of mankind, children and adolescents have been violated their rights, being victims of various types of violence and experiences of abuse. Over time and in the face of some changes, violence has become more visible and Psychoanalysis has been obtaining significant results dealing with this problem. Objectives: To investigate and describe how the psychoanalytic approach contributes to the effective monitoring of children who have been sexually abused. Method: The study was outlined by the Bibliometric method, which is characterized by a quantitative and statistical technique that measures the indices of production and spread of scientific knowledge. Seventeen articles were selected for comprising this session. Initially, a quantitative analysis of the material was performed through bibliometric indicators, which resulted in the following data: number of authors per research; repetition of authors' names by search; number of articles published per year in the related area; percentage of publications per year and the language used in the publications of the articles analyzed. Subsequently, the main psychoanalytical contributions to child sexual abuse were described. Results and Discussion: Psychoanalysis is based on a care Ethics when approaching child sexual abuse in the clinic to promote and guarantee the child empathy, hospitality and listening. Also, to provide a welcoming and trusting environment, so that the victim can reconstruct his/her experience and, above all, resignify his/her history. Conclusion: Psychoanalysis has provided relevant contributions regarding the understanding of child sexual abuse; since, through its premises, it has pointed out essential aspects of this approach on the care toward the victim - such as, Child Sexuality, the Oedipus Complex; it highlights the concept of trauma, and finally, it ranks the scores on the therapist's role in dealing with the child who has been sexually abused.